Electron-capture and beta-decay modes with realistic nuclear structure calculations - Giannaka, P. G.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2012)
In this work, we concentrate on the e-capture and β-decay processes in isotopes that are important for searching the explosive nucleosynthesis in massive stars. To this aim, we improved our codes which use compact analytical expressions for the required reduced matrix elements of all basic multipole operators (isospin repre- sentation). The ground state of the nuclear isotopes chosen, is constructed in the context of the BCS method while their excited states are calculated by solving the QRPA equations, using as residual two-body interactions that of the Bonn C-D one-meson exchange potential. We focus on the role of the charged Gamow-Teller and Fermi transitions in Fe group nuclei that are the main constituents of the core in presupernovae formation.